1979
DOI: 10.1093/nar/7.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a limited set of proteins with different mRNAs and protection of 5′-caps against pyrophosphatase digestion in initiation complexes

Abstract: A variety of 5'-3H-methyl-labeled, oxidized viral mRNAs were used as probes for detecting in wheat germ initiation complexes proteins that interact with, and can be cross-linked to, the 5'-cap structure. A limited and reproducible set of specific proteins was obtained with the different mRNAs. The binding of these proteins to the 5'-end of mRNA apparently results in protection against nucleotide pyrophosphatase digestion of the cap even in initiation complexes in which the 5'-end is susceptible to pancreatic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Cross-linking of the cap (Sonenberg et al 1979a) and the nucleotide at the +2 position from the cap (Lindqvist et al 2008) with an eIF3 subunit of a similar molecular weight has been reported previously and was attributed to eIF3d (Lindqvist et al 2008). We, however, identified the cap-interacting subunit as eIF3l.…”
Section: Translation Initiation On Capped Mrnassupporting
confidence: 75%
See 1 more Smart Citation
“…Cross-linking of the cap (Sonenberg et al 1979a) and the nucleotide at the +2 position from the cap (Lindqvist et al 2008) with an eIF3 subunit of a similar molecular weight has been reported previously and was attributed to eIF3d (Lindqvist et al 2008). We, however, identified the cap-interacting subunit as eIF3l.…”
Section: Translation Initiation On Capped Mrnassupporting
confidence: 75%
“…Consistently, cross-linking of the cap and eIF4E is inefficient in cellfree extracts (Sonenberg and Shatkin 1977;Sonenberg et al 1979a), and it was also suggested that, during initiation, the eIF4E-cap interaction is disrupted (Sonenberg et al 1979b). According to our model, the most likely stage at which eIF4E is released from the cap is the beginning of attachment, when dissociation would be required to avoid steric hindrance as mRNA enters the mRNAbinding channel.…”
Section: Translation Initiation On Capped Mrnassupporting
confidence: 67%
“…eIF3 can be UV cross-linked to ␤-globin and other mRNAs in binary complexes (Fig. 3F, lane 1; Sonenberg et al 1979;Setyono et al 1984;Westermann and Nygard 1984). It can also be UV cross-linked to […”
Section: Stimulation Of Stable Binding Of Eif3j− To 40s Subunits By Omentioning
confidence: 99%
“…Exceptions are the RNAs of picornaviruses (2-4) and some plant viruses (5,6). In crude protein-synthesizing systems several polypeptides (cap-binding proteins, CBPs) were shown to crosslink specifically to the cap structure (7). In addition, a Mr 24,000 polypeptide that binds to the cap structure has been identified in partially purified initiation factor fractions (8) and purified by affinity chromatography on m7GDP-Sepharose (9).…”
mentioning
confidence: 99%